COSMOS-E: Guidance on conducting systematic reviews and meta-analyses of observational studies of etiology. - Olaf M Dekkers; Jan P Vandenbroucke; Myriam Cevallos; Andrew G Renehan; Douglas G Altman; Matthias Egger (PLoS Medicine)
Background To our knowledge, no publication providing overarching guidance on the conduct of systematic reviews of observational studies of etiology exists. Methods and findings Conducting Systematic Reviews and Meta-Analyses of Observational Studies of Etiology (COSMOS-E) provides guidance on all steps in systematic reviews of observational studies of etiology, from shaping the research question, defining exposure and outcomes, to assessing the risk of bias and statistical analysis. The writing group included researchers experienced in meta-analyses and observational studies of etiology. Standard peer-review was performed. While the structure of systematic reviews of observational studies on etiology may be similar to that for systematic reviews of randomised controlled trials, there are specific tasks within each component that differ. Examples include assessment for confounding, selection bias, and information bias. In systematic reviews of observational studies of etiology, combining studies in meta-analysis may lead to more precise estimates, but such greater precision does not automatically remedy potential bias. Thorough exploration of sources of heterogeneity is key when assessing the validity of estimates and causality. Conclusion As many reviews of observational studies on etiology are being performed, this document may provide researchers with guidance on how to conduct and analyse such reviews.